Partisipasi Masyarakat dalam Proses Pembentukan KUHP Nasional untuk Mewujudkan Negara Kesejahteraan sebagai Hukum Responsif - Lawrencya, Sheryn; Anisa, Tasya (Veteran Law Review, 2023)
The formation of legal products becomes a necessity in responding to the interests of society. The formation of regulations determines whether they are able to distribute comfort and welfare to the community or cause conflict. Get aspirations and agreements from the community is a form of responsive law. The participation of all elements of society is important in the process of producing legal products, especially the National Criminal Code which has been drafted since 1963, but there are still many controversial articles and cause debate in society. This writing uses research methods and data collection techniques in a normative juridical way to find better law and offer solutions to legal problems, by descriptive critical analysis with document study. DPR as the representative of the society has an important role in accommodating and following up on the aspirations of the society. Able to recognize the public's desire to realize the concept of a welfare state and responsive law. Further evaluation needs to be carried out in the legislative process by including the aspirations of the society.